P074 SZN-1326 promotes colonic mucosal healing in an acute injury model of IBD by first accelerating epithelial regeneration and secondarily reducing inflammation. (21st January 2022) - Fletcher, R; Xie, L; Phipps, J; Sanman, L; Deshmukh, S; Shah, D; Hill, N; Liu, A; Gupta, S; Sura, A; Chen, H; Ye, J; et al.
Abstract: Background: Wnt signaling plays critical roles in regulating intestinal stem cell maintenance and differentiation. The inflammatory bowel disease, ulcerative colitis (UC), is characterized by epithelial lesions, and there is a need for therapies that promote mucosal healing in addition to limiting inflammation. The Surrozen proprietary Wnt mimetic, SZN-1326, is a FZD5, 8 and LRP6-specific, full-length, effectorless, bi-specific IgG1 molecule that is well-suited for impacting the intestinal epithelium where FZD5 is highly expressed. Previously, we have shown that in an acute dextran sodium sulfate (DSS) epithelial injury model, where 4% DSS was provided in the drinking water for seven days followed by 1% DSS until termination at day 10, a single dose of SZN-1326 at 1 mg/kg or higher on Day 4 robustly induced intestinal epithelial healing and reduced inflammation, and we wanted to understand more thoroughly the mechanism underlying this activity. Methods: Here, we report on additional studies in the same DSS model including scRNA-seq and tissue analysis timepoints at days 3, 4, 5, 6, 7, and 10 (6-days post treatment). Results: DSS impacted all tissue layers by day 3. The direct effect of SZN-1326 on the epithelium occurred as early as 24-hours after treatment (day 5 of the experiment). SZN-1326 induced and/or increased Wnt target and cell cycle gene expression in the epithelium leading to progenitor cell expansion, and following this wave of enhanced progenitor proliferation, the cells transited toward colonocyte differentiation more quickly than the progenitor cells in control treated samples. Even in the presence of 1% DSS, relative to the anti-GFP treatment samples, the absorptive cell lineage in the SZN-1326-treated epithelium was more similar at a transcriptomic level to the uninjured condition. In addition, when comparing SZN-1326 treatment to anti-GFP at 24-hours, there were no differentially expressed genes in either the stroma or immune cells. However, analysis of the later timepoints revealed a robust reduction in cytokine/inflammatory signaling in the stromal and immune cells and a drastic reduction of infiltrating monocytes and neutrophils, which we validated in the tissue by immunohistochemistry. We detected this reduction by 72-hours after treatment, and it was more pronounced by day 10, 6-days after treatment, implicating a secondary effect. Conclusion: In this acute damage context, SZN-1326 promoted mucosal healing by transiently inducing epithelial progenitor cell expansion and accelerating epithelial repair. Secondary to its initial impact on the epithelium, SZN-1326 reduced stromal and immune cytokine signaling and immune cell infiltration.